Удосконалення електроерозійної головки розмірної обробки дугою на базі настільного свердлувального верстата з ручною подачею електрода-інструмента - Сергєєв, А. О.; Боков, В. М.; Шмельов, в. м.; Sergeev, А.; Bokov, V.; Shmelov, V. (ЦНТУ, 2023)
Запропоновано самогальмувальну передачу в якості механізму керування ручною подачею електрода-інструмента для електроерозійної головки розмірної обробки дугою на базі настільного свердлувального верстата. Показано, що використання такої електроерозійної головки дозволяє покращати її експлуатаційні характеристики за рахунок розвантаження оператора від осьових зусиль при керуванні та підвищити якісні показники обробки шляхом зменшення кількості коротких замикань та підвищення точності керування. Currently, in mechanical engineering, the nomenclature of processed materials and the shape of processed products stimulate the use of various types of electrical processing of metals. The most common of them is electropulse treatment. The cost of a modern electric pulse machine is estimated at hundreds of thousands of dollars. In addition, this method of processing uses as an energy carrier an electric spark or an electric pulse that burns in the end interelectrode gap with pauses. During a pause, the part is not processed, therefore, the electropulse method of processing does not provide the maximum possible processing productivity. At the same time, the conditions of repair factories and workshops do not require high processing precision, but require cheaper equipment and high processing performance. A highly productive method of dimensional processing of metals with an electric arc is known.
Improvement of the EDM Head for Dimensional Processing With an Arc on the Basis of a Desktop Drilling Machine With Manual Feeding of the Electrode-Tool
Keywords: електроерозійна головка; розмірна обробка дугою; настільний свердлувальний верстат; валшестерня рейкової передачі; черв’ячна передача; EDM head; dimensional arc machining; table drilling machine; rack gear shaft; worm gear